ON THE MODELLING OF LEPROSY PREVALENCE IN SOUTH SULAWESI USING SPATIAL AUTOREGRESSIVE MODEL - Rezki Melany Sabil; Ray Sastri (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2020)
The prevalence of leprosy is the number of leprosy cases per 10.000 peoples. Based on data from the Ministry of Health, the highest prevalenece of leprosy was in South Sulawesi. This is needs a special attention because leprosy is a contagious disease. The number of leprosy cases in an area may be influenced by the number of leprosy case in the neighbor area due to the movement of the air. So that, the location of area need to be included in analysis of leprosy. The aim of this study is to identify the variables that spatially affect the prevalence of leprosy in South Sulawesi and modelling it. This study uses data from the Ministry of Health for year 2016. The method of analysis is Spatial Autoregressive Model (SAR). The results is There is a positive spatial autocorrelation in the prevalence of leprosy in district level, which means that regions with high prevalence of leprosy are surrounded by areas with high prevalence of leprosy, and vice versa. The prevalence of leprosy in an area is influenced by the prevalence of leprosy in neighbor districts, the percentage of BCG vaccines recipient and the percentage of households with healthy lifestyle.